2018
DOI: 10.1002/aelm.201800155
|View full text |Cite
|
Sign up to set email alerts
|

Pressure‐Induced Metallization and Robust Superconductivity in Pristine 1T‐SnSe2

Abstract: Band engineering in layered metal dichalcogenides leads to a variety of physical phenomena and has obtained considerable attention recently. In this work, pressure‐induced metallization and superconductivity in pristine 1T‐SnSe2 is reported via electrical transport and synchrotron X‐ray diffraction experiments. Electrical transport results show that the metallization emerges above 15.2 GPa followed by appearance of superconducting transition at 18.6 GPa. The superconductivity is robust with a nearly constant T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 46 publications
(93 reference statements)
2
35
0
Order By: Relevance
“…In addition, a series of representative selenides with similar layered structures (e.g., InSe, GaSe, ReSe 2 and SnSe 2 ) have also been reported to undergo the phase transition of metallization under high pressure, and therefore, the pressure-induced metallization maybe widely existing in most of selenides. [31][32][33][34]…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a series of representative selenides with similar layered structures (e.g., InSe, GaSe, ReSe 2 and SnSe 2 ) have also been reported to undergo the phase transition of metallization under high pressure, and therefore, the pressure-induced metallization maybe widely existing in most of selenides. [31][32][33][34]…”
Section: Resultsmentioning
confidence: 99%
“…[7,14b,197] Some 2D metal chalcogenides exhibit natural superconductivity. [23b,198] High pressure can also induce superconductivity in pristine SnSe 2 . Moreover, charge density waves usually exist in these 2D metal chalcogenides with superconductivity.…”
Section: Versatile Device Applicationsmentioning
confidence: 99%
“…As one of the fundamental state parameters, pressure is an effective and clean way to tune the lattice constant, crystal structure, and electronic state, thus varying the fundamental physical properties of materials. Regarding the pressure engineering of photovoltaic and optoelectronic materials, various exotic phenomena have been revealed recently, including photoluminescence (PL) emission enhancement, prolonged carrier lifetime, bandgap optimization, and superconductivity [14][15][16][17][18][19][20][21] . For the photovoltaic material ZnSiP 2 , Bhadram et al 22 reported that it undergoes a phase transition from tetragonal to cubic rock-salt structure between 27 and 30 GPa, in agreement with the ab initio investigations 23 .…”
Section: Introductionmentioning
confidence: 99%